Elements of money and banking: With reference to the Tanzanian economy - E.J.M. Wiketye (Research, Information and Publication Department, 2025)
The book is divided into six parts and sixteen chapters. Part I consists of chapters one to four. Chapter one provides an introduction to essentials of money and banking. This is followed by Chapter Two which outlines the historical development of money and banking. Chapter Three outlines the general attributes of money. Specifically, the chapter concentrates on the definition and functions of money. The demand for money is the subject matter of Chapter Four. Here, the meaning of "holding money" is discussed, followed by a general formulation of the Demand for Money. The chapter ends with a brief discussion of theories of the demand for money. Specifically, the quantity theory (old and new) and the Keynesian theory are investigated. Part II is about monetary theory. It consists of Chapter Five and Six Chapter Five outlines the basic monetary propositions. Chapter Six analyses the expenditures, incomes and prices. The chapter starts the analysis from the demand (expenditure) side of the economy, and then looks at the supply side. It ends with an examination of monetary and fiscal policies. Part III deals with Commercial and Central Banking. Chapter Seven provides the theoretical basis of commercial banking in a simplified single bank-model. Chapter Eight looks at the structure of commercial banking in Tanzania in a historical perspective. Chapter Nine looks at the concept of central banking. First, the evolution and functions of central banking are examined. Then the chapter ends up looking at the concept of monetary policy. Chapter Ten examines central banking in Tanzania, with specific reference to the historical development of the Bank of Tanzania. By Part IV looks at non-bank financial intermediaries. This part consists of chapters eleven and twelve. Chapter Eleven looks at financial intermediation in a theoretical perspective. Specifically the chapter examines the functions of financial markets and the role of financial intermediaries. Chapter Twelve outlines the financial intermediation in Tanzania. Essentially, it looks at the major financial institutions in the country. Part V deals with money and the economy. It consists of two chapters. Chapter thirteen looks at monetary expansion and inflation. The chapter treats both long-run and short-run implications of monetary expansion. Chapter Fourteen gives a brief account of the Post-World War II inflation process. Specifically, the chapter looks at the concept of "creeping" inflation and also looks at some measures to control inflation. Part VI looks at the international scene. In Chapter Fifteen the concept of balance of payments, in a simplified manner, is examined in relation to (i) fixed exchange rate systems and (ii) floating exchange rate systems. Then Chapter Sixteen looks at the international financial crisis and the collapse of Fixed Exchange Rate System. The chapter starts with a brief outline of the so-called gold-standard system and ends up with an examination of the Bretton Woods System and why it collapsed. Each chapter except the introductory chapter ends up with one or more discussion questions.